Study of the Influence of Electronic Word of Mouth (eWOM) and Perception of Government Support on Interest and Motivation for Mobile Banking Adoption to Increase Financial Inclusion in Indonesia - Ketut Alam Wangsa Wijaya; Gita Gayatri (Eduvest - Journal of Universal Studies, 2025)
Financial inclusion has emerged as a pivotal strategy to drive sustainable economic growth and reduce inequality in developing economies. In Indonesia, more than 66 million adults remain excluded from formal financial systems. This study investigates how Electronic Word of Mouth (eWOM) and perceived government support affect behavioral intention and motivation to adopt mobile banking, with the broader aim of promoting financial inclusion. Drawing from the Technology Acceptance Model 3 (TAM3), Prospect Theory, and Financial Inclusion Theory, the study proposes a structural model that incorporates perceived usefulness, perceived ease of use, perceived risk, perceived cost, and trust as mediators influenced by eWOM. A total of 252 unbanked respondents across six Indonesian regions were surveyed, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results show that perceived usefulness, ease of use, and risk significantly predict behavioral intention to adopt mobile banking. eWOM has a strong impact on shaping perceptions of trust and usefulness, while perceived government support significantly moderates the effect of perceived usefulness and risk on intention. The findings underscore the value of digital advocacy and policy alignment in overcoming adoption barriers and fostering inclusive financial ecosystems.